Risk and Prevalence of Self-Perceived Voice Disorders in Male and Female University Professors - Kyriakou, Kyriaki; Petinou, Kakia; Phinikettos, Ioannis (My University, 2018)
Purpose: The aim of this survey was to explore risk factors and prevalence of voice disorders in male and female university professors in order to determine the need for a gender specific preventative vocal hygiene education program which could improve their occupational performance. Methods: An online survey was filled out by 102 female and 94 male university professors from 12 universities in Cyprus. The survey obtained information on risk factors that may lead to voice problems related to general health, voice use, lifestyle, and environment, as well as, the self-perceived severity of a participant’s voice difficulty. The chi-squared test was applied to investigate the differences in answers for each voice risk factor between male and female professors. The prevalence of self-perceived voice disorders in males and females was also calculated. Results: The estimated prevalence of self-perceived voice disorders was 43.1% for female and 26.6% for male professors. Female professors were more likely to “frequently” experience respiratory infections, “sometimes” speak over their natural breath cycle, and “always” and “frequently” have stress and anxiety than males. Female faculty were also more likely to have breaks between classes that last less than 30 minutes. Conclusions: Risk factors for developing voice disorders in female professors are related to health, voice use and lifestyle. Therefore, a preventative gender specific vocal hygiene education program is recommended for female faculty.
Keywords: Risk factors; Voice disorders; Prevalence; Male; Female; University professors; Cyprus